2019
DOI: 10.2147/opth.s228777
|View full text |Cite
|
Sign up to set email alerts
|

<p>Maximum Medical Therapy: Brinzolamide/Brimonidine And Travoprost/Timolol Fixed-Dose Combinations In Glaucoma And Ocular Hypertension</p>

Abstract: IntroductionMaximal medical therapy (MMT) is the use of ≥3 classes of topical anti-glaucoma agents to achieve maximal intraocular pressure (IOP) reduction while minimizing adverse effects and compliance challenges.PurposeTo evaluate the additive IOP-lowering effect of twice-daily brinzolamide 1%/brimonidine 0.2% fixed-dose combination (BBFC) used adjunctively with once daily travoprost 0.004%/timolol 0.5% fixed-dose combination (TTFC) in patients with open-angle glaucoma (OAG)/ocular hypertension (OHT).Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…Previous studies in the literature reported adverse drug reactions similar to those in our study after BBFC. 7 , 15 , 16 , 17 , 18 , 19 , 20 Similar to our study, Lerner et al 7 , reported that the rate of ocular adverse effects was 11.9% in patients who received maximum medical therapy in the form of BBFC and a beta-blocker/PG analog. In the same study, ocular adverse effects were observed in 7.5% of the control group given the beta-blocker/PG analog combination alone.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies in the literature reported adverse drug reactions similar to those in our study after BBFC. 7 , 15 , 16 , 17 , 18 , 19 , 20 Similar to our study, Lerner et al 7 , reported that the rate of ocular adverse effects was 11.9% in patients who received maximum medical therapy in the form of BBFC and a beta-blocker/PG analog. In the same study, ocular adverse effects were observed in 7.5% of the control group given the beta-blocker/PG analog combination alone.…”
Section: Discussionsupporting
confidence: 89%
“…In a few recent studies, patients received a maximum medical therapy regimen of BBFC together with a beta-blocker/PG combination. Lerner et al 7 evaluated maximum medical therapy by investigating the additive efficacy of BBFC with travoprost/timolol fixed combination in 67 open-angle glaucoma and OHT patients and observed a statistically significant reduction in IOP in the group to which BBFC was added. Joh and Jin 18 divided patients who received maximum medical therapy into two groups, triple (dorzolamide-timolol combination + brimonidine + latanoprost) and double (tafluprost/timolol combination + BBFC) maximum therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jin and Lee 15 reported that in a study involving cases of normal tension glaucoma treated with BBFC, the mean IOP decreased from 17.1±1.4 mm Hg to 12.4±1.8 mm Hg. In a study of the efficacy of a combination of travoprost/timolol with the addition of BBFC, Lerner et al 19 found a 4.25 mm Hg reduction of IOP after 6 weeks of treatment from baseline of 21.6 mm Hg, which was significantly better than that of the control group. Topouzis et al 20 added a combination of brinzolamide (1%)/brimonidine (0.2%) to PG and reported that the IOP reduced to 5.59 mm Hg from the baseline of 22.8 mm Hg after 6 weeks of treatment, as compared with that of the control group, showing a significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] The additional IOP lowering effect of BBFC on the existing therapy (0.004% travoprost/0.5 % timolol fixed-dose combination) was reported to be 2.15 mm Hg. [ 13 ] Because these IOP-lowering effects were measured by GAT and the baseline IOP was over 18 mm Hg, they cannot be directly compared to our NTG case. However, it is generally believed that even if the measurement device was the iCare HOME, the drug effects similar to those evaluated by the GAT could be obtained in individual cases by increasing the frequency of measurements.…”
Section: Discussionmentioning
confidence: 99%